The German School and its Critical Horizons: Reception Theory as a Model (Journal of the College of Basic Education, 2025)
The German school has contributed to many critical breakthroughs. It is one of the most important European schools that created an intellectual turning point in the course of modern European critical research. Her critical achievement was met with a cognitive response throughout the world. Although German thinkers were the last of the great nations to pay attention to critical study, as the French school was in the last classical stage, and the English school began to reap the fruits of its modern critical theories that it had established, and distinct critical trends emerged from the Russian school that relied on the production of Russian literature in the nineteenth century, German philosophers and thinkers quickly compensated for this temporal decline with remarkable enthusiastic progress, a persistent pursuit of knowledge, and a philosophical mind that was constantly searching and thinking, starting with Kant, who sought to inaugurate a critical era whose slogan was the brave use of reason, then Husserl, who soon turned criticism into phenomenology, and ending with the pioneers of reception theory (Jauss and Iser). Phenomenology is considered one of the most important cognitive principles from which the theory of reception crystallized, and this theory represents the pinnacle of what German criticism has reached.